Unraveling the Heterogeneity of Tumor Immune Microenvironment in Hepatocellular Carcinoma by SingleCell RNA Sequencing and its Implications for Prognosis and Therapeutic Response - Han, Ying; Song, Lele; Lv, Lingna; Fan, Chunlei; Ding, Huiguo (Turkish Journal of Gastroenterology, 2024)
Abstract Tumor immune microenvironment (TIME) has become a new hotspot in cancer research over the past few years. Tumor immune microenvironment of hepatocellular carcinoma (HCC) is especially intriguing as HCC is reported to be highly heterogeneous by previous genomic and cytological studies. It is also closely related to patient prognosis and therapeutic outcome. The recently emerged single-cell RNA sequencing (scRNAseq) technique provides a new tool for TIME study, and current studies have made great advances in defining the roles of TIME in HCC pathogenesis and therapy. Current evidence suggests that heterogeneity is a key player influencing therapeutic response, drug resistance, and prognosis. However, our understanding is limited on the roles of TIME heterogeneity in HCC development, prognosis, and therapeutic response, especially in the era of immunotherapy. This review aims to unravel the heterogeneity of TIME in HCC by scRNAseq, with specific focuses on the cellular, transcriptional, and marker perspectives of TIME heterogeneity in HCC, as well as assessing prognostic and therapeutic response by heterogeneity markers. By summarizing current discoveries regarding TIME heterogeneity, we hope to provide clues on the crucial roles of various cellular components in the development and progression of HCC. We also hope to identify potential markers and therapeutic targets for prognosis assessment and personalized treatment to improve patient outcomes. Combined therapies from multiple dimensions regarding heterogeneity may provide new opportunities to treat HCC more effectively. Cite this article as: Han Y, Song L, Lv L, Fan C, Ding H. Unravelling the heterogeneity of tumor immune microenvironment in hepatocellular carcinoma by single-cell RNA sequencing and its implications for prognosis and therapeutic response. Turk J Gastroenterol. 2024;35(12):876-888.